Optimation Front Upright Racing Car Using Finite Element Analysis - Fitra Bagus Hendi Prabowo; Rizaldy Hakim Ash-Shiddieqy; Winarto; Nur Husodo; Mahirul Mursid; Bayu Adhi Saputro (Institut Teknologi Sepuluh Nopember, 2022)
Upright is part of the car's suspension system that plays an important role in creating and comforting the car. Supporting driving safety, upright components must be designed to be light but strong to withstand loading when the car is in conditions of acceleration, deceleration and cornering. Not only strong as a benchmark, but components must also be lightweight, so we need a method, namely a topology optimization method. Using finite element software makes the optimization process very easy and very fast with maximum accuracy. The process is by inputting the model from CAD software, defining materials, input constraints and vector styles, meshing process, and finally the solution process. From the simulation results, it will be known the value of the solution in the form of stress, deformation and safety factor of the upright component. From several topology optimization designs, they will be compared to find out which is the best design which will be used as a design recommendation. By referring the result, 43% mass reduction is the best optimum design, its safety factor is 4.956.